C-erbB2 (Her-2/neu) gene amplification in women with breast cancer – initial studies - Kulig, Andrzej; Smolarz, Beata; Kozłowska, Elżbieta; Romanowicz-Makowska, Hanna; Zadrożny, Marek (Menopause Review/Przegląd Menopauzalny, 2002)
Background. The c-erbB2 (Her2/neu) oncogene is located on the long arm of chromosome 7, encoding for a 185 kD transmembrane glycoprotein p185 with tyrosine kinase receptor function. Several studies have shown that overexpression of c-erbB2 (Her-2/neu) gene has been associated with breast cancer appearance. The aim of the present study was to investigate the relationship between amplification of c-erbB2 gene and the appearance of breast cancer in menopausal women. Materials and methods. Paraffin embedded tumour tissue were obtained from patients with breast cancer (n=20). Blood samples from age matched healthy women (n=20) served as control. The amplification of c-erbB2 gene was determined by PCR reaction using the allele specific primers. Results. The amplification of c-erbB2 gene was significantly higher in patients compared as control (p<0.05). Conclusion. The results suggest that amplification of c-erbB2 gene may be linked with appearance of breast cancer in menopausal women.